2016
DOI: 10.1186/s12245-016-0106-7
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of early progression to severe sepsis or shock among emergency department patients with nonsevere sepsis

Abstract: BackgroundProgression from nonsevere sepsis—i.e., sepsis without organ failure or shock—to severe sepsis or shock among emergency department (ED) patients has been associated with significant mortality. Early recognition in the ED of those who progress to severe sepsis or shock during their hospital course may improve patient outcomes. We sought to identify clinical, demographic, and laboratory parameters that predict progression to severe sepsis, septic shock, or death within 96 h of ED triage among patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
52
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 42 publications
4
52
1
2
Order By: Relevance
“…We found that for each hour that passed between ED triage and antimicrobial administration, the risk of progression to septic shock increased by 8.0%, highlighting the importance of early identification and treatment of patients with infection-induced organ dysfunction. The percentage of patients progressing to septic shock in our study was slightly higher than previously reported (6,7,8, 14,15). This is likely because we did not include patients with sepsis, defined as infection + SIRS (ICD-9 diagnosis code 995.91), and because our patients required the presence of an ICD-9 diagnosis code for severe sepsis or septic shock.…”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations
“…We found that for each hour that passed between ED triage and antimicrobial administration, the risk of progression to septic shock increased by 8.0%, highlighting the importance of early identification and treatment of patients with infection-induced organ dysfunction. The percentage of patients progressing to septic shock in our study was slightly higher than previously reported (6,7,8, 14,15). This is likely because we did not include patients with sepsis, defined as infection + SIRS (ICD-9 diagnosis code 995.91), and because our patients required the presence of an ICD-9 diagnosis code for severe sepsis or septic shock.…”
Section: Discussioncontrasting
confidence: 89%
“…Holder et al investigated predictors of early progression to severe sepsis or septic shock in patients who presented to the ED with sepsis (infection + SIRS) but without signs of organ dysfunction(7). Their cohort excluded patients with severe sepsis at triage – the specific patient group that we desired to study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypoalbuminemia has been proposed as a useful predictor of morbidity and mortality in many different clinical settings such as community-acquired pneumonia [12] and hemodialysis and coronary heart disease [13]. As a negative acute phase protein, initial serum albumin was also independently associated with disease progression to severe sepsis [14] and 30-day mortality in emergency medical patients, irrespective of the cause [15, 16]. …”
Section: Introductionmentioning
confidence: 99%
“…Such work will require highly granular adjustment for hospital- and patient-level risk factors. Ultimately, it may yield personalized triage approaches that are based not only on such formative work but also incorporate genetic predispositions [5] and real-time biomarkers [6] to help predict individual risk of clinical decompensation and ultimately “net ICU benefits”.…”
mentioning
confidence: 99%